Drivers of Farmers’ Intention to Use the Digital Agricultural Management System: Integrating Theory of Planned Behavior and Behavioral Economics - Sun, Sangluo; Wen, Xiaowei; Jie, Siqiong; Gao, Qihua; Zhu, Ying; Wen, Simei (Frontiers in Psychology, 2022)
China's fishery industry has national and international relevance whose aquaculture production account for more than 60 percent of the world's total aquaculture production. But the average amount of pesticides used per hectare in China is roughly five times of the world average. The abuse of chemical fertilizers and drugs have brought chronic, long-term and cumulative harm to both human beings and environment. The digital agricultural management system should be adopted to reduce nonnegligible environment pollution and the quality and safety risks of aquatic products. So, it is essential to understand the factors that may influence the adopt intention of this digital management approaches. The present study aimed to examine the adopting intention of farmers toward the digital agricultural management system using two theories – the theory of planned behavior (TPB) and the behavioral economics – as the research framework. The population was composed of farmers in the provinces of Guangdong province in south China of whom 219 farmers were sampled with stratified random sampling technique. Structural equation modelling was used to analyze the data and it was revealed that this research framework could potentially predict intention. And we observed that the two biased belief of availability bias and loss aversion bias can be the main predictive influence factors of responsible behaviors in adopting the digital agriculture management system, which highlights the importance of framing recommendations in terms of losses rather than gain may be more effective to increase farmers’ intention to adopt the digital system on their farms.